Innovations on the horizon: teledentistry, artificial intelligence, and hybrid models to improve oral health for vulnerable communities - Drafta, Sergiu; Macris, Andrei; Petre, Alexandru E. (Frontiers in Oral Health, 2025)
ObjectivesVulnerable populations experience substantial challenges accessing dental care, leading to disproportionate oral health burdens. Digital solutions, such as teledentistry and artificial intelligence, offer new opportunities to improve access, quality and effectiveness of the care.MethodsThis paper presents a narrative literature review incorporating findings from peer-reviewed journals, systematic reviews, and case studies retrieved from PubMed, Scopus, and Web of Science (2013–2024). Evidence was also synthesized using the artificial intelligence tool Elicit to include high-quality data on teledentistry, artificial intelligence and hybrid dental care models, focusing on their implementation and effectiveness. Studies were selected to address relevance for underserved populations and digital innovation in dental care delivery.ResultsTeledentistry modalities, including e-consults and virtual dental homes, have demonstarte enhanced access and delivery of preventative care. Artificial intelligence tool provide accurate diagnoses, predict treatment needs, and streamline workflows. Hybrid models combining virtual screening with in-person treatment bridge care gaps and enhance continuity and efficiency, particularly for underserved populations.ConclusionsThe integration of teledentistry, artificial intelligence and hybrid dental practice models offers a transformative approach to improving oral health care acces and equity. However, success will require investment, support and collaboration to scale these innovations effectively.